Ecological significance of protected areas in the tropical mountains of Eastern Africa - Marco Andrew Njana (Ecological Indicators)
Protected areas (PAs) are a tool and strategy for achieving multiple forest management objectives. This study employed ecological indicators to evaluate the effectiveness of PAs in tropical mountains of Eastern Africa. The study also assessed the performance of existing height-diameter allometries and developed new height-diameter allometries. The study was conducted in the Eastern Arc Mountains (EAMs) located in East Africa. Fifty percent of all recorded tree species were exclusively concentrated in the PAs category I. Tree dimensions and species diversity were also outstandingly higher in the PA category I than in the PA category IV and other land uses. The species-specific structure of the tree population in the PA category I was an inverse J-shape, which implies a large number of trees in smaller diameter classes and tree frequencies decrease as diameter classes increase. However, this was not the case for the PA category IV and other land uses. Furthermore, carbon storage varied statistically significantly between PA categories and between PAs and other land uses where PA category I had disproportionally higher carbon storage. The study also highlights that carbon pools are either affected positively or negatively by ecological and physical factors. The newly developed height-diameter allometries out-performed the existing allometries hence improving the prediction of tree height and biomass in the EAMs. The bottom line of this study is that the PAs in tropical mountains in Eastern Africa and beyond are critical in the conservation of tree species and have net positive effects on forest structure, carbon storage and other ecosystem services. However, at a minimum effectiveness of PAs is dependent on optimal supply of management resources, conservation action planning and successful execution of conservation action plans. The study also provides policy and management recommendations.